Tugas Perkembangan Pra Remaja Ditinjau dari Peran Ayah dan Ibu - Hanim Nuril Rahmatul Alifia; Nanik Kholifah; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
Pre-adolescent development tasks occur in children aged 6-12 years, through social interactions driven by the support and praise of the nearest person children will develop a sense of pride about abilities, eradicate Creativity, train skills, have responsibilities and build a sense of competence. The phenomenon that happens is the role of father and mother that is invisible in the task of pre-adolescent development on the subject. In addition, the subject's behavior is like saying harsh, bullying and feeling ruled by the possibility is a form of compensation for the subject's failures in the development stage. This phenomenon shows that this is important to watch. This research is aimed at finding out the role of pre-adolescent development underpinned by the role of father and mother. This research was carried out in the Market Capital area, the subject of the research was two brothers who lived with her ears. This study uses interview and observation methods, to verify data inactivity using triangular methods. Research shows that on informant 1 (NE) the pre-adolescent development task currently passed by the subject still needs intensity and commitment in a support and command from the nearest. While research on informant 2 (AL) shows that the pre-adolescent development task that the subject is currently undergoing is going well enough even though there is no father and mother role in the subject.